Accessing of the mixed-valence states in the zinc meso-ferrocenylporphyrin: experimental and theoretical data. - Nemykin, V.N.; McGinn, M.; Kqposov, A.Y.; Tretyakova, I.N.; Polshin, E.V.; Loim, N.M.; Abramova, N.V. (Украинский химический журнал, 2005)
The formation of the stable at room temperature mixed-valence state in the zinc 5,10,15,20-tetra(ferrocenyl)porphyrin has been investigated by UV-V1S-NIR, Mossbauer, NMR, electrochemical, and theoretical (DFT) methods. On the basis of experimental and theoretical data it has been concluded that the first oxidation process involves.